Equity, Equality, and Reform in Contemporary Public Education - Grant, Marquis C., editor (Hershey PA : Information Science Reference, 2018)
"This book explores why equality and equity are often mischaracterized as interchangeable terms in public education. It discusses equity, including historical and social contexts of equity, rationale for continued focus on equality, school reform as a form of equity and the how a Eurocentric curriculum prohibits an equitable distribution of resources and opportunities in modern education"